Figurative Language in the Album "The Tortured Poets Department" by Taylor Swift - Mailani Salsabila; Niken Kencana, Ungu (LingPoet: Journal of Linguistics and Literary Research, 2024)
This study is aims to identified, analyze, and figure out the meaning of each figurative language used in song lyrics of â€œThe Tortured Poets Departmentâ€ album by Taylor Swift. The data include the lyrics of 16 songs in Taylor Swiftâ€™s album â€œThe Tortured Poets Departmentâ€. This study employed content analysis method where the data is gathered by gathering all the lyrics of Taylor swift's songs in â€œThe Tortured Poets Departmentâ€ album. The findings was revealed that eleven from thirteen figurative language from Perrineâ€™s theory was used in this album: simile, metaphor, personification, synecdoche, metonymy, symbol, allegory, paradox, hyperbole, irony, and allusion. Simile had 14%, metaphor had 4,3%, personification had 4,3%, synecdoche had 3,2%, metonymy had 20,4%, symbol had 11,8%, allegory had 1,0%, paradox had 2,1%, hyperbole had 15,0%, irony had 18,0%, and allusion had 5,3%. Metonymy is a figurative language that most used in the â€œThe Tortured Poets Departmentâ€ song lyrics. Â